Is phenomenal consciousness really a special case in science? - Gärtner, Klaus; Cordovil, João L. (Frontiers in Psychology, 2024)
In the metaphysics of science, it is often held that higherlevel properties are grounded in micro-physical properties. According to many philosophers, however, phenomenal consciousness resists this view. Many famous arguments in Philosophy of Mind have been given to reject this notion. In this paper, we argue that there is something odd about the idea that phenomenal consciousness is a special case for science and give a constructive proposal on how consciousness can fit in the natural world. To do so, we will first introduce a general notion of what grounding is. Then, we will briefly explain how the arguments for the specialness of phenomenal consciousness work by considering two famous examples, namely the zombie and the knowledge argument. In a further step, we will briefly discuss two cases from other areas in science, i.e. in particle physics and chemistry. We will demonstrate that the standard view about the reductive relation does not hold, even in these paradigm cases of the natural sciences. If what we argue is true, we think that most arguments from phenomenal consciousness cannot defeat physicalism per se. Finally, we will introduce an alternative way to naturalize phenomenal consciousness.